The GALANTE photometric survey of the northern Galactic plane: project description and pipeline. Issue 3 (2nd July 2021) - Maíz Apellániz, J; Alfaro, E J; Barbá, R H; Holgado, G; Vázquez-Ramió, H; Varela, J; Ederoclite, A; Lorenzo-Gutiérrez, A; García-Lario, P; García Escudero, H; García, M; Coelho, P R T
ABSTRACT: The GALANTE optical photometric survey is observing the northern Galactic plane and some adjacent regions using seven narrow- and intermediate-filters, covering a total of 1618 deg 2 . The survey has been designed with multiple exposure times and at least two different air masses per field to maximize its photometric dynamic range, comparable to that of Gaia, and ensure the accuracy of its photometric calibration. The goal is to reach at least 1 per cent accuracy and precision in the seven bands for all stars brighter than AB magnitude 17 while detecting fainter stars with lower values of the signal-to-noise ratio. The main purposes of GALANTE are the identification and study of extinguished O+B+WR stars, the derivation of their extinction characteristics, and the cataloguing of F and G stars in the solar neighbourhood. Its data will be also used for a variety of other stellar studies and to generate a high-resolution continuum-free map of the H α emission in the Galactic plane. We describe the techniques and the pipeline that are being used to process the data, including the basis of an innovative calibration system based on Gaia DR2 and 2MASS photometry.